The Chinese learner : cultural, psychological, and contextual influences (Australian Council for Educational Research, 1996)
Learning theories and approaches to research. The cultural context for Chinese learners. Western misperception of the Confucian-heritage learning culture. Memorizing and understanding. Accepting personal responsibility for learning. Hong Kong secondary school learners...